The more basic isoform of eEF1A relates to tumour cell phenotype and is modulated by hyper‐proliferative/differentiating stimuli in normal lymphocytes and CCRF‐CEM T‐lymphoblasts. Issue 2 (29th August 2012) - Scaggiante, Bruna; Dapas, Barbara; Pozzato, Gabriele; Grassi, Gabriele
Abstract The elongation factor 1A proteins (eEF1A1/A2) are known to play a role in tumours. We previously found that a more basic isoform of eEF1A (MBI‐eEF1A) is present in the cytoskeletal/nuclear‐enriched extracts of CCRF‐CEM T‐lymphoblasts but not in those of normal lymphocytes. To obtain deeper knowledge about MBI‐eEF1A biology, we investigate from which of the eEF1A proteins, eEF1A1 or eEF1A2, MBI‐eEF1A originates and the possibility that its appearance can be modulated by the differentiated or proliferative cell status. CCRF‐CEM T‐lymphoblasts and normal lymphocytes were cultured with or without differentiation/pro‐proliferative stimuli (Phorbol 12‐Myristate 13‐Acetate (PMA) alone or the combination of phytohaemagglutinin (PHA) with PMA, respectively), and the presence of MBI‐eEF1A evaluated together with that of the eEF1A1/A2 mRNAs. Our data indicate that the MBI‐eEF1A may derive from eEF1A1 as eEF1A2 is not expressed in CCRF‐CEM and normal lymphocytes. Moreover, MBI‐eEF1A is inducible in normal lymphocytes upon hyper‐proliferative stimuli application; in CCRF‐CEM, its presence can be abrogated by PMA‐induced differentiation. Finally, MBI‐eEF1A may have a functional role in hyper‐proliferating/tumour cells as its disappearance reduces the growth of CCRF‐CEM and that of PHA/PMA‐stimulated lymphocytes. The presented data suggest that MBI‐eEF1A may be related to oncogenic cell phenotype, rising the possibility to use MBI‐eEF1A as target for novel therapeutic strategies. Copyright © 2012 John Wiley & Sons, Ltd.